Monitoring and Analysis of a High-Performance Concrete Shaft Lining: A Case Study - Daolu Quan; Hongguang Ji; Xiaobo Su; Hui Cao; Juanhong Liu (Advances in Materials Science and Engineering)
Shaft lining in ultradeep mines on the coast of eastern China under the complex external environments of “high in situ stress and high osmotic pressure” has the disadvantages of failure; to solve this problem, the field test of high-performance concrete shaft lining structure was carried out in Sha-ling gold mine. The field test study of the high-performance concrete shaft lining was carried out in a −1120 m ingate and a −1114 m to −1124 m shaft. Its stress and deformation were monitored and analyzed. The maximum compressive stress of the HPC shaft lining structure at the level of −1117.7 m of the air intake shaft is 1.91 MPa. Based on the Von-Mises yield theory and the analytical solution of thick-walled cylinder theory, the ultimate limit of the high-performance concrete shaft lining in the Sha-ling gold mine was obtained. The high-performance concrete shaft lining strain changes smoothly, and concrete strain can be divided into three stages: the rapid growth period, the slow growth period, and the stable period. The monitoring results show that the high-performance concrete shaft lining has excellent mechanical properties in the external environment of high in situ stress, which can be used as a reference for the support design of similar projects.